PEMBELAJARAN ANAK BERBAKAT (GIFTED AND TALENTED) - Priyono, Priyono (Jurnal Inovasi Pendidikan, 2011)
Learning Gifted and Talented (Gifted and Talented) at Muhammadiyah Elementary School Special Program. Special Education Studies Program, Department of Science Education, Faculty of Teacher Training and Education, University of Surakarta Eleven March. The purpose of this study is to know the implementation of teaching gifted children in elementary school in Surakarta Muhammadiyah Special Programs. Subjects were all students 5 th grade Special Programs Surakarta Muhammadiyah school year 2009/2010. Data collection techniques using the method of observation, interviews, and documentation. Data analysis techniques used by triangulation by performing kros - check on the results of observation, interviews and documentation with an interactive model. The study concluded that: (1) the implementation of teaching in primary schools together with the Special Programme Muhammadiyah elementary school in general, (2) There are significant differences in the way of learning that can be seen from the existence of extra time, materials, learning resources which are many, varied learning methods, and the teacher field of study, (3) The emphasis of service delivery enrichment, acceleration and grouping.